Spin configurations and switching in magnetic nanostructures. - Chandra Junus, William. (2010)
In this project, ferromagnetic nanowires and nanotubes of lengths 500nm to 1250 nm and diameters between 200nm and 300 nm were simulated with the Object Oriented MicroMagnetic Framework (OOMMF) software. The spin configurations as well as the hysteresis loops obtained from the simulation were then investigated and discussed and the domain wall motion and reversal process were then observed and compared. From the simulations, it was found that nanotube structures have a unique capability to form a double loop hysteresis profile when its aspect ratio (AR) – ratio between the length and the outer diameter - is low, whereas nanowires will give an almost linear hysteresis profile if it was simulated on low AR. This phenomenon was then attributed to the hollow center structure of nanotubes which allows magnetization cells from one side of the tube to behave independently from that of the other side of tube. Then, the crystal anisotropy factors were also added to the simulation and the its effect on the reversal process and the hysteresis loop were also discussed.